2019
DOI: 10.1101/521682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autophagy regulates the localization and degradation of p16INK4a

Abstract: The tumor suppressor protein p16 INK4a (p16) is a well-established hallmark of aging that induces cellular senescence in response to stress. Previous studies have focused primarily on p16 regulation at the transcriptional level; comparatively little is known about the protein's intracellular localization and degradation. The autophagy-lysosomal pathway has been implicated in the subcellular trafficking and turnover of various stressresponse proteins, but it is unclear whether p16 is involved in these pathways.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…A third mechanism by which cells can clear and recycle cellular components is by autophagy. Many types of protein aggregates are cleared by autophagy, including τ, Aβ, α-synuclein, huntingtin, SOD1 and p16 INK4A [38][39][40][41][42][43], with autophagy defects leading to neurodegenerative disease [44,45].…”
Section: Clearance Of Protein Aggregatesmentioning
confidence: 99%
“…A third mechanism by which cells can clear and recycle cellular components is by autophagy. Many types of protein aggregates are cleared by autophagy, including τ, Aβ, α-synuclein, huntingtin, SOD1 and p16 INK4A [38][39][40][41][42][43], with autophagy defects leading to neurodegenerative disease [44,45].…”
Section: Clearance Of Protein Aggregatesmentioning
confidence: 99%
“…Interestingly, p16 protein levels were increased in IHH cells in the refeeding experiment ( Figure 4D-E), suggesting that p16 is regulated post-translationally. A recent report demonstrated that p16 is degraded by autophagy (17). Accordingly, rapamycin treatment for 8h in IHH cells led to a strong decrease of p16 protein ( Figure 4F), suggesting that autophagy-mediated p16 degradation likely links nutritional status to p16 activity in hepatocytes.…”
Section: P16 Protein Expression Is Modulated By Nutritional Changes Imentioning
confidence: 65%
“…We observed that p16 protein level is increased in IHH cells during refeeding conditions, without modulation of p16 mRNA expression by fasting. In line, p16 protein was recently demonstrated to be degraded by autophagy (17), a process induced by fasting and inhibited by refeeding (31,32). Moreover, partial deletion of ATG5 in mice, resulting in inhibition of autophagy, increased p16 protein levels in the liver (33).…”
Section: Discussionmentioning
confidence: 94%
“…Besides promoter regulation, p16 is degraded by protease in the nucleus in lung cancers 32 and by autophagy in the cytosol of neurons 33 . Preliminary data revealed that FAM111, a protease responsible for p16 degradation in lung cancer 32 was expressed in CRCs (data not shown); p16 expression may be regulated by these pathways.…”
Section: Discussionmentioning
confidence: 99%